Investigation of oil palm empty fruit bunches in biosoda pulping by tropical white-rot fungi, Ganoderma australe (Fr.) Pat - Mohamad Hasnul., B; Noorlidah, A.; Vikineswary, S.; Md. Yusoff, M. (Malaysian Society of Applied Biology, 2015)
Ganoderma australe, a white-rot fungus, is well-known as a decomposer of logs and stumps in the Malaysian forest. We investigated G. australe (KUM60848) strain for production of ligninolytic enzymes i.e. lignin peroxidase (LiP) and laccase, and hydrolytic enzymes, i.e. cellulase and xylanase, using oil palm empty fruit bunches (EFB) in solid-substrate fermentation (SSF). EFB was shown to support good mycelial growth for G. australe during 28 days of solid-substrate fermentation. All tested enzyme activities demonstrated highest activities of LiP (0.18±0.02 U/ml), laccase (1.92±0.03 U/ml), cellulase (0.72±0.11 U/ml) and xylanase (0.42±0.01 U/ml) throughout the 28 days of incubation. Compared to an untreated control, the pretreated EFB yield increased to a maximum of 18% during biopulping. Fourteen days of SSF had the highest degree of material dissolved, as shown by pulp yields and the optimum values (29.8 Nm/g tensile index and 2.73 Kpa m2/g burst index) acceptable to obtain paper sheets.